The clustering of galaxies in the SDSS-III Baryon Oscillation Spectroscopic Survey: measuring DA and H at z = 0.57 from the baryon acoustic peak in the Data Release 9 spectroscopic Galaxy sample. Issue 1 (30th January 2014) - Anderson, Lauren; Aubourg, Eric; Bailey, Stephen; Beutler, Florian; Bolton, Adam S.; Brinkmann, J.; Brownstein, Joel R.; Chuang, Chia-Hsun; Cuesta, Antonio J.; Dawson, Kyle S.; Eisenstein, Daniel J.; Ho, Shirley; et al.
Abstract: We present measurements of the angular diameter distance to and Hubble parameter at z  = 0.57 from the measurement of the baryon acoustic peak in the correlation of galaxies from the Sloan Digital Sky Survey III Baryon Oscillation Spectroscopic Survey. Our analysis is based on a sample from Data Release 9 of 264 283 galaxies over 3275 square degrees in the redshift range 0.43 <  z  < 0.70. We use two different methods to provide robust measurement of the acoustic peak position across and along the line of sight in order to measure the cosmological distance scale. We find D A (0.57) = 1408 ± 45 Mpc and H (0.57) = 92.9 ± 7.8 km s −1  Mpc −1 for our fiducial value of the sound horizon. These results from the anisotropic fitting are fully consistent with the analysis of the spherically averaged acoustic peak position presented in Anderson et al. Our distance measurements are a close match to the predictions of the standard cosmological model featuring a cosmological constant and zero spatial curvature.